Preparing for a paradigm shift in aging populations: listen to the oldest old. Issue 1 (1st January 2018) - Komatsu, Hiroko; Yagasaki, Kaori; Kida, Hisashi; Eguchi, Yoko; Niimura, Hidehito
ABSTRACT: Purpose : Current healthcare systems are not suitable for serving future societies in which the oldest old are commonplace. The objective of this study was to understand what the oldest old care most about in their daily lives. Methods : Semi-structured in-depth interviews and thematic analysis were used. Face-to-face interviews were conducted in 17 elderly residents (≥ 95 years) of Arakawa-ku, Tokyo, Japan from July to November 2017. Results : Three themes emerged from the interview responses: "unshakable beliefs and social ties, " "natural acceptance, " and "my day-to-day life with precious moments." The oldest old strongly believe in diligence and compassion and maintain strong relationships with people around them. Despite their small social networks, they are concerned about future society. They accept their selves and their lives, including their impending deaths. Despite their functional decline, they control their lives by making very small decisions. They live on a moment-to-moment basis, cherishing simple events. Conclusion : Maintaining autonomy through making small decisions and enjoying small pleasures are important to the oldest old. Understanding the needs of the oldest old is the first step towards developing optimal geriatric care for an aging population.